NLP in action : attention mechanism and upgrading TorchText 0.9. - Lane, Hobson (Manning Publications, 2022)
Hobson updated Geoff's Chapter 12 PyTorch examples for training an encoder-decoder to translate between English and German or maybe even Ukrainian. Torchtext version 0.9 deprecated the `Field` and `Bucket` classes. These have been replaced by the `DataLoader` class built into pytorch directly. We no longer need customized abstractions to build torch natural language training sets!.